OBTAINING OF COMPLEX FERTILIZERS BASED ON CONVERSION OF PHOSPHORIC ACID GYPSUM PULP (Scientific journal of the Fergana State University, 2023)
Studies have been carried out to obtain complex fertilizers based on suprefos pulp, NH4NO3 and KCl at pH = 5.25 and 60°С and mixing time of 120 min. As a result of granulation and drying, high-quality complex fertilizers were obtained with a content of 17.76% SO3, 18.71% N; 18.88%, 17.08% SO3, 7.02% N; 18.53% Р2О5tot.; 18.42% K2O and 14.34% N; 13.91% Р2О5tot.; 13.81% K2O, 12.98% SO3, corresponding to grades N : P = 1 : 1, N : P : K = 0.4 : 1 : 1 and 1 : 1 : 1 with a high degree of conversion equal to 93.66 ; 97.78 and 99.61%. Judging by the content of SO3 in the range of 12.98-17.76%, they can also be called NPS- and NPKS-fertilizers. The salt composition was studied by radiography, in which dicalcium phosphate, nitrate, sulfate and phosphate of ammonium and potassium were found.